2010
DOI: 10.1186/1471-2148-10-314
|View full text |Cite
|
Sign up to set email alerts
|

The imprint of the Slave Trade in an African American population: mitochondrial DNA, Y chromosome and HTLV-1 analysis in the Noir Marron of French Guiana

Abstract: BackgroundRetracing the genetic histories of the descendant populations of the Slave Trade (16th-19th centuries) is particularly challenging due to the diversity of African ethnic groups involved and the different hybridisation processes with Europeans and Amerindians, which have blurred their original genetic inheritances. The Noir Marron in French Guiana are the direct descendants of maroons who escaped from Dutch plantations in the current day Surinam. They represent an original ethnic group with a highly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 87 publications
3
48
0
1
Order By: Relevance
“…A recent phylogenetic study suggests that West African hepatitis B virus (HBV) lineages were introduced to Haiti during the peak years of slave movement (1). Similarly, recent studies of human T-cell leukemia virus type 1 (HTLV-1), which sometimes combine human and viral evidence, have indicated that Surinamese, Guyanan, Brazilian, Argentinian, and Peruvian HTLV-1 lineages grouped among West African lineages (3,12,32).…”
Section: Discussionmentioning
confidence: 99%
“…A recent phylogenetic study suggests that West African hepatitis B virus (HBV) lineages were introduced to Haiti during the peak years of slave movement (1). Similarly, recent studies of human T-cell leukemia virus type 1 (HTLV-1), which sometimes combine human and viral evidence, have indicated that Surinamese, Guyanan, Brazilian, Argentinian, and Peruvian HTLV-1 lineages grouped among West African lineages (3,12,32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mitochondrial DNA profile of this population is closer to that of Africans than to those of most other African Americans with 99.3% of the haplotypes being of African origin i.e., belonging to haplogroup L lineages. It is closely linked with West African haplogroups (L2a1, L1b, L3d, L3f1), just as their non-recombinant Y chromosome haplotypes (E1b1a7*, E1b1a8*) and HTLV-1 sequence analysis indicate a major origin on the Gold Coast and the Bight of Benin (Brucato et al, 2010).…”
Section: Specific Characteristics Of the 3 Subsets Of Patientsmentioning
confidence: 98%
“…Latin America is a region where the most dramatic human migrations have taken place, from the early northeastern Asian bands of hunter-gatherers that conquered the last continent humanity had expanded to [12], through the 16th and 17th centuries European colonization and bringing of sub-Saharan African (SSA) slaves [13], to the latest waves of immigrants from all over the world in the last two centuries [14]. This complex population history makes present Latin American Populations (LAP) possibly the most ethnically diverse on the planet.…”
Section: Introductionmentioning
confidence: 99%